The Steady Hand of an Ecstatic Seer, Part 1 John’s Literary Genius in Communicating His Visionary "Apokalypsis" - Korner, Ralph J. (2023)
The apparently disorganized visionary content of the book of Revelation suggests a disoriented and perhaps even psychotropic visionary. Nonetheless, the ecstatic Seer’s literary record of that apocalyptic journey is a multi-valent masterpiece that uses three literary devices simultaneously to recount a linear narrative and a reiterative structure. This two-part article focuses, in part 1, upon how John’s use of the "space/time referent" and the linguistic equivalents of the two clauses "and I saw" and "after these things I saw" also elucidate coherent structures for Jewish prophetic visionary texts, and, in part 2, upon how they provide structure for Jewish apocalypses. Distinctive to John’s Apocalypse, however, is the fact that it leverages those three literary devices to create a reiterative structure that serves implicitly to reinforce his explicit statements to his seven "ekklēsia" communities that the return of Jesus the Jewish "Christos" was imminent.
Keywords: Apocalypse; Prophecy; Revelation; Space-time; Vision